ANALISIS SETTING RELE OGS SEBAGAI SISTEM PENGAMAN TRANSFORMATOR 3 UNTUK MENJAGA KONTINYUITAS ALIRAN DAYA DI GARDU INDUK PESANGGARAN - I Wayan Alit Wigunawan; I Gede Dyana Arjana; Cok Gede Indra Partha (Jurnal SPEKTRUM, 2017)
Transformer 3 of Pesanggaran Substation obtains additional power plants with a maximum power of 60 MW. Power generation is used to supply the load of feeders in Substation of Pesanggaran and also channeled to 150 kV transmission system at Substation of Pesanggaran through Transformator 3 to Substation of Nusa Dua to assist power supply at Nusa Dua Substation. If there is a feeders interruption in the Substation of Pesanggaran which causes the load of feeders to be disconnected, then the power from the generator that is flowed to the 150 kV system increases. Thus the Transformer 3 works heavier, resulting in the current and temperature of the transformer also increased. Increased temperatures in the transformer for long periods can result in damage and reduced lifetime of the transformer. From the problems then calculation of current and working time OGS and OCR as the Transformer 3 safety system. The result of calculation of OGS setting of phase1 is 1600 A with setting work time of 2 seconds, phase 2 is 1700 A with setting working time of 1,5 seconds and stage 3 of 1800 A with setting work time of 1 second. The OGS relay characteristic is definite. For OCR at 150 kV side, the current setting is 277 A and setting time is 1.36 seconds, while OCR setting at 20 kV side is obtained by setting current of 2078.4 A and setting time of 1.18 seconds with OCR Relay characteristic used is inverse.